ANALISIS PENGELOLAAN DANA BOS PADA SMP DI RAYON PARIGI KABUPATEN PARIGI MOUTONG - Hatika, Hatika (Katalogis, 2015)
This reserch aims to determine and analyze: 1) the management of BOS fund in secondary schools of Rayon Parigi, Parigi Moutong Regency; 2) supporting factors and constraints in the management of BOS fund in secondary schools of Rayon Parigi, Parigi Moutong Regency. Data is collected from questionnaires and analyzed with descriptive statistics. The results indicate that the management of BOS fund in secondary schools of Rayon Parigi, Parigi Moutong Regency is in good category with mean values for each sub variabels as follow: planning of 4.13, financing of 4.22, bookkeeping of 4.53, controlling of 4.21 and financial accoutability of 4.42. The result also implies the existence of supporting factor and constraints in managing BOS fund in secondary school of Rayon Parigi, Parigi Moutong Regency. The supporting factors are socialisation of BOS fund, monitoring by local management team of BOS fund, and the availability of technical instruction of BOS fund management. Some contraints addressed are: lack of skills in the preparation of planninf documents, lack of spending compliance, lack of supervision, and untimely submissions of reports.